Trend FOMO Mahasiswa UIN Suska Riau - Labibah Azzahra; Nurmansyah Nurmansyah; Maisya Putri; Aldi Juliaska; Sukma Erni (Pusat Riset dan Inovasi Nasional, 2024)
This study investigates the trend of Fear of Missing Out (FOMO) among students at UIN SUSKA Riau. FOMO, defined as the anxiety that others might be having rewarding experiences from which one is absent, is increasingly common in the digital era, especially among university students who are frequent social media users. The research aims to explore the prevalence and effects of FOMO on students' academic performance, mental health, and social interactions. A mixed-methods approach was utilized, with data gathered from online surveys and in-depth interviews involving 300 students across various faculties. The results indicate that a significant portion of students experience moderate to high levels of FOMO, which is strongly associated with intensive social media usage. Students reported that FOMO adversely impacts their focus and academic performance, leading to procrastination and heightened stress levels. Furthermore, FOMO contributes to feelings of inadequacy and anxiety, as students often compare their lives to the idealized representations they encounter online. The study underscores the necessity for awareness and intervention programs to aid students in managing their social media usage and alleviating the negative impacts of FOMO. Addressing these concerns can help UIN SUSKA Riau cultivate a healthier and more supportive academic environment. This research adds to the growing body of literature on digital well-being and student mental health, highlighting the importance of balanced social media engagement.